DEVOLOPING STUDENT’S BOTH PROVING AND CREATIVE SKILLS USING SIEVE OF EROTOSPHENE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article presents the remarkable possibilities and advantages of sieve of Erotostphenes in the teaching of mathematics. It has been shown to have a positive effect on students ’perfect understanding of the rules of division.